Are African Traditional Religions Demonic? - Byamukama, Joseph; Jude 3 Project (2025)
In this eye-opening episode, Lisa Fields sits down with Dr. Joseph Byamukama, a New Testament scholar from Uganda, to explore the deep roots of African spirituality, its misconceptions in the West, and its complex relationship with Christianity. They unpack key themes from Dr. Byamukama's powerful chapter in Apologetics in Africa, including African understandings of a supreme creator, the role of ancestors, polygamy, witchcraft, and the theological bridge Christianity can offer through the resurrection. This is a must-watch for anyone interested in contextual theology, African traditions, or the resurgence of African spiritual practices in the diaspora.
free